Forcible measures for maritime law enforcement by the coast guard - Wang, Jinhu; Wei, Yichao; Su, Xin (Frontiers in Marine Science, 2025)
The particularity of the maritime law enforcement environment and the complexity of the content of forcible measures determine the importance of the standardized application of forcible measures for maritime law enforcement by the coast guard. Maritime forcible measures mainly include administrative forcible measures, criminal forcible measures, and the use of force. The timely and reasonable application of forcible measures by the coast guard in specific maritime law enforcement can achieve the purposes of protecting maritime security, safeguarding maritime rights and order, and guaranteeing procedures and human rights. It is of great significance in effectively strengthening the effectiveness of maritime law enforcement. Forcible measures must be based on the requirements of restraint of law enforcement powers, temporary measures, and a last resort in law enforcement. When imposing forcible measures, it is essential to clearly define the purposes and boundaries for the coast guard to employ such measures, adhere to the principles of due process, proportionality, freedom of navigation, and reasonable prudence, and enhance the development of law enforcement capabilities and continuously improve the effectiveness and professionalism of law enforcement practices.